2020
DOI: 10.3389/fimmu.2020.578732
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Inflammatory Bowel Disease Among Patients With Ankylosing Spondylitis: A 13-Year Population-Based Cohort Study

Abstract: Aim Ankylosing spondylitis (AS) primarily affects the axial skeleton and extraarticular structures. Small-scaled studies have reported that the incidence and prevalence of inflammatory bowel disease (IBD) are higher in patients with AS than in the general population. This study determined the incidence of IBD in patients with AS using a large scale population-based cohort dataset. Methods This was a retrospective cohort study. Patient data were collected from the Taiwan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…A study from the United States reviewed the status of solid cancer in elderly patients with AS from 1999 to 2010 and found that the risk of esophageal cancer, gastric cancer, and lung cancer was lower and the risk of melanoma, urinary system cancer, and breast cancer was higher [24] . Two other studies have similar findings [25,26] . Combined with the enrichment results of this study, there may be similar pathways but different feedback mechanisms between AS and different tumors, especially colon cancer, gastric cancer, and other gastrointestinal cancers.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A study from the United States reviewed the status of solid cancer in elderly patients with AS from 1999 to 2010 and found that the risk of esophageal cancer, gastric cancer, and lung cancer was lower and the risk of melanoma, urinary system cancer, and breast cancer was higher [24] . Two other studies have similar findings [25,26] . Combined with the enrichment results of this study, there may be similar pathways but different feedback mechanisms between AS and different tumors, especially colon cancer, gastric cancer, and other gastrointestinal cancers.…”
Section: Discussionsupporting
confidence: 62%
“…[ 24 ] Two other studies have similar findings. [ 25 , 26 ] Combined with the enrichment results of this study, there may be similar pathways but different feedback mechanisms between AS and different tumors, especially colon cancer, gastric cancer, and other gastrointestinal cancers. This may have important implications for the treatment and prognosis of the disease.…”
Section: Discussionmentioning
confidence: 59%
“…Based on Taiwan National Health Insurance Research Database (NHIRD) from 2005 to 2012, the overall incidence of IBD was lower in the AS group than in the non-AS group, but without reaching statistical significance (1.41 vs. 1.79 per 1000 person-years, incidence rate 0.79, 95% CI 0.48–1.28; p = 0.332) [ 113 ]. Interestingly, another retrospective cohort study based on the same database from 2000 to 2012 showed that patients with AS had a higher risk of IBD than the non-AS group in the subgroup aged < 40 years (HR: 2.85, 95% CI: 1.51–5.40) [ 114 ].…”
Section: Spa With Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Typically, the sacroiliac joints are also affected [9], and occasionally other joints such as the shoulders or hips are involved [10]. Eye and bowel problems may also occur [11,12]. Inflammatory low back pain that is intermittent in nature is a characteristic symptom of AS [9].…”
Section: Introductionmentioning
confidence: 99%